Numerical simulations of corrosion processes. Properties of the corrosion front and formation of islands - Vautrin-Ul, C.; Chausse, A.; Stafiej, J.; Badiali, J.P. (Condensed Matter Physics, 2004)
Using a one-parameter model and a cellular automaton description we investigate the formation of a cavity in a material for which a small area has been deprotected and put in contact with an aggressive environment. Corrosion processes take place in a medium where the diffusion is assumed to be very rapid. We investigate the mean size of the cavity, the roughness of the corrosion front, the chemical composition of the front and the formation of islands resulting from the detachment of pieces of material. For the simulation times that we have investigated, a stationary regime is observed in which the relative composition of the front and the roughness become constant. An increase of the roughness produces the islands which leads to a smoothing of the front, and thus the roughness exhibits a maximum value. A mean field approach quite satisfactoryly reproduces the combination of processes involved in the corrosion model. Although we consider a one-parameter model, some results such as the value of roughness and its maximum are difficult to predict in a quantitative way.